Pubic Osteomyelitis: Epidemiology and Factors Associated with Management Failure in Two French Reference Centers. (4th October 2017) - Ferry, Tristan; Becker, Agathe; Valour, Florent; Perpoint, Thomas; Boussel, Loic; Ruffion, Alain; Laurent, Frederic; Senneville, Eric; Chidiac, Christian; ,
Abstract: Background: Pubic osteomyelitis (PO) is a neglected bone and joint infections (BJI), as its management is still poorly codified. We aim to describe PO epidemiology and to look for factors associated with management failure. Methods: We performed a retrospective cohort study in two French reference centers including patients with PO in 2010–2016. Treatment failure was defined by clinical (persistence or recurrence of clinical signs) and/or microbiological failure. Factors associated with treatment failure were determined by univariate Cox analysis (hazard ratio [HR] and 95% confidence interval calculation). Kaplan–Meier curve was compared between groups by log-rank test. Results: Twenty-five patients were included over 13 years (median age 67 years; 19 men, median ASA score 3). Six (24 %) had a PO from haematogenous origin. Those were all monomicrobial infection, due to S.aureus, mostly identified in young patients without comorbidities, especially in athletes. No surgery was required if no abcess or bone sequestrum were found. Nineteen patients (76 %) had a post-operative chronic PO (developed from 1 month to 11 years after a pelvic surgery); 15 of them had history of pelvic cancer (60%); 12 received radiotherapy at the site of infection (48 %). Infection was polymicrobial in 68 % of cases, including 32 % of cases with multidrug-resistant pathogens. A clinical success was recorded in only 14 patients (56%). Treatment failure was always noticed in chronic post-operative forms. Potential risk factors associated with failure management were: pelvic cancer history (HR 3.8; P = 0, 089); pelvic radiotherapy history (HR 2.9; P = 0.122); clinical sinus tract (HR 5.1; P = 0, 011); infection with multidrug-resistant bacteria (HR 2.8; P = 0, 116), and polymicrobial infection (HR 70.5; P = 0, 090). Conclusion: Our study highlights predominant chronic complex post-operative forms of PO. They are mostly plurimicrobial, sometimes associated with multi-drug resistance, occurring in fragile patients with pelvic cancer. It frequently leads to complex antibiotherapy, with important risk of relapse. Aggressive surgical procedure with large bone resection is frequently required in patients who underwent pelvic radiotherapy. Disclosures: T. Ferry, HERAEUS: Consultant, Speaker honorarium. E. Senneville, 1959: Board Member and Consultant, Consulting fee and Speaker honorarium